MiRNA profiling of human naive CD4 T cells links miR‐34c‐5p to cell activation and HIV replication. (19th December 2016) - Amaral, Andreia J; Andrade, Jorge; Foxall, Russell B; Matoso, Paula; Matos, Ana M; Soares, Rui S; Rocha, Cheila; Ramos, Christian G; Tendeiro, Rita; Serra‐Caetano, Ana; Guerra‐Assunção, José A; Santa‐Marta, Mariana; et al.
Abstract: Cell activation is a vital step for T‐cell memory/effector differentiation as well as for productive HIV infection. To identify novel regulators of this process, we used next‐generation sequencing to profile changes in microRNA expression occurring in purified human naive CD4 T cells in response to TCR stimulation and/or HIV infection. Our results demonstrate, for the first time, the transcriptional up‐regulation of miR‐34c‐5p in response to TCR stimulation in naive CD4 T cells. The induction of this miR was further consistently found to be reduced by both HIV‐1 and HIV‐2 infections. Overexpression of miR‐34c‐5p led to changes in the expression of several genes involved in TCR signaling and cell activation, confirming its role as a novel regulator of naive CD4 T‐cell activation. We additionally show that miR‐34c‐5p promotes HIV‐1 replication, suggesting that its down‐regulation during HIV infection may be part of an anti‐viral host response. Synopsis: miR‐34c‐5p is a novel player in TCR‐stimulated human naive CD4 T cells, emerging as a common link between cell activation and HIV replication. Its down‐regulation on HIV‐1 or HIV‐2 infection may be an anti‐viral cell response to limit HIV production. miR‐34c‐5p is a novel regulator of TCR‐mediated naive CD4 T‐cell activation. Small RNA‐seq reveals stable miR levels in human naive CD4 T cells exposed to HIV. HIV infection of TCR‐activated naive CD4 T cells results in miR‐34c‐5p down‐regulation. miR‐34c‐5p overexpression promotes HIV replication. Abstract : Transcriptional up‐regulation of miR‐34c‐5p upon TCR stimulation is involved in T‐cell differentiation, while its down‐regulation during HIV infection may be part of an anti‐viral host response.